Membrane-intercalating conjugated oligoelectrolytes impact on bioelectrochemical systems - Yan, Hengjing (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.